2014
DOI: 10.1093/infdis/jiu083
|View full text |Cite
|
Sign up to set email alerts
|

γδ T cells and CD14+ Monocytes Are Predominant Cellular Sources of Cytokines and Chemokines Associated With Severe Malaria

Abstract: Early/innate PBMC responses to pRBC in vitro are informative as to cytokines/chemokines associated with SM. Predominant cellular sources are monocytes and γδ T cells. Monocyte-derived chemokines support a role for monocyte infiltrates in the etiology of SM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(104 citation statements)
references
References 36 publications
3
100
1
Order By: Relevance
“…al. recently demonstrated a decrease in iRBC-stimulated expression of genes encoding pro-inflammatory cytokines and chemokines in children after their first malaria infection of the season ( 3, 19 ). Because these analyses were performed on bulk unfractionated PBMCs, the cellular subsets responsible for this blunted inflammatory response were not identified.…”
Section: Discussionmentioning
confidence: 99%
“…al. recently demonstrated a decrease in iRBC-stimulated expression of genes encoding pro-inflammatory cytokines and chemokines in children after their first malaria infection of the season ( 3, 19 ). Because these analyses were performed on bulk unfractionated PBMCs, the cellular subsets responsible for this blunted inflammatory response were not identified.…”
Section: Discussionmentioning
confidence: 99%
“…Brain endothelial cells and astrocytes have been found to express CXCL10 in response to P. berghei ANKA infection (19,20), and high levels of this chemokine have been detected in cerebrospinal fluid of children who succumbed to P. falciparum-mediated CM (14). In addition to brain tissue, recent field studies in malaria-endemic areas revealed strong associations between PBMC-derived CXCL10 and severe malaria, suggesting a role for leukocyte-derived CXCL10 in the development of disease syndromes (34). Consistent with that concept, in this study we found that hematopoietic cell-derived CXCL10 controls leukocyte recruitment to the brain, is responsible for the development of CM, and has a detrimental effect on the control of parasite biomass.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to DCs, effector CD8+ T cell response is inhibited during H5N1 viral infection by IL-10 producing CD8+ Treg cells [75,76]. The induced manipulation toward the Th2 profile assures increased surviving possibility for different infective agents, such as viruses, chlamydias, and parasites [65, 67-69, 73,74,[77][78][79]. The early IL-10 production by T cell, B cell, and monocyte/macrophage (but not on NK and DC) activation can lead to chronicity of lymphocytic choriomeningitis and B hepatitis virus infections, and the IL-10-mediated early T cell Similarly to viral infections, parasite-induced IL-10 production by various immune cells is associated with impaired resistance to protozoan and nematodes [80,81,86,87].…”
Section: Principal Immune Conditionsmentioning
confidence: 99%